Spaces and Strategies of Resistance: Cultural Movements in the French West Indies (AmeriQuests, 2021)
The objective of this article is to examine the socio-spatial springboards that enabled the inhabitants of a popular district to mobilize. Based on a long-term field survey (2011-2018) conducted in Fort-de-France,Martinique, Iexamine the spatial dimension of collective action strategies and repertoires and their conditions and difficulties of implementation.From the 1960s onward, some inhabitants of this district managed to make their drums resound in the heart of the carnival of Fort-de-France, and reinvented original music and revalued certain local cultural traditions threatened with destruction, in particular by creating the marching band Tanbo Bô Kannal. To understand this mobilization, this paper introduce space as a central dimension of the collective action of deprived groups, by questioning the mechanisms by which individuals and groups play with each other in the spaces and places they conceive, manage, or invest.